Effects of Brassica rapa L. Polysaccharides on Bile Acid Metabolism and Intestinal Microbiota in Humanized Mice - ZHANG Mengying, TI Jiayi, LI Wei, BI Kaiyue, WU Yuhan, LI Yanbo, ZHAO Yu, WANG Wei (Shipin Kexue)
Objective: To investigate the regulatory effect of Brassica rapa L. polysaccharides (BRAP1-1) on the metabolism of bile acids and the intestinal microbiota in a humanized mouse model. Methods: The mouse model was established by long-term oral administration of human fecal suspension, followed by intragastric administration of BRAP1-1 at low (50 mg/kg, LB) and high (200 mg/kg, HB) doses, the same volume of physiological saline as the blank control (CK) or inulin as the positive control (100 mg/kg, IN). After three weeks, body mass, organ indexes, serum biochemical indicators including triglyceride (TG), total cholesterol (TC), and malondialdehyde (MDA) levels, colonic tissue structure, bile acid composition in feces, intestinal microbiota composition, and short-chain fatty acids (SCFAs) contents were examined and analyzed. Results: Compared with the CK group, body mass decreased, and thymus index significantly increased in the three treatment groups (P < 0.05). Spleen index was significantly higher in the HB and IN groups than in the CK and LB groups (P < 0.05), indicating that BRAP1-1 had certain effects on mouse body mass and organ indices. Different concentrations of BRAP1-1 reduced the levels of TC, TG, and MDA, thereby regulating lipid metabolism. Furthermore, BRAP1-1 enhanced colonic villus development, and high-dose of BRAP1-1 intervention significantly increased the total bile acid level in mouse feces, modulated the intestinal microbiota composition by altering α and β diversity, increasing the relative abundance of beneficial bacteria such as Lysinibacillus, Solibacillus, Rikenellaceae_RC9_gut_group, and Bacteroides, and decreasing the relative abundance of harmful bacteria including Treponema and Flavobacterium. Concurrently, the contents of acetic acid, propionic acid, butyric acid, and isobutyric acid in feces were also significantly upregulated (P < 0.05). Conclusion: BRAP1-1 effectively regulates bile acid metabolism and the intestinal microbiota structure in mice, enhancing the production of beneficial SCFAs in the intestine. This study provides theoretical insights into the promotion of intestinal health and bile acid metabolism by BRAP1-1, offering new perspectives for the deep processing of B. rapa and the development of related functional foods.